2020
DOI: 10.1002/bmc.5038
|View full text |Cite
|
Sign up to set email alerts
|

What is necessary for next‐generation atmospheric environmental standards? Recent research trends for PM2.5‐bound polycyclic aromatic hydrocarbons and their derivatives

Abstract: The air pollution associated with PM 2.5 kills 7 million people every year in the world, especially threatening the health of children in developing countries. However, the current air quality standards depend mainly on particle size. PM 2.5 contains many carcinogenic/mutagenic polycyclic aromatic hydrocarbons (PAHs) and their derivatives such as nitropolycyclic aromatic hydrocarbons and oxygenated PAHs. Among them, environmental standards and guidelines have been set for benzo[a]pyrene by few

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Air pollution causes millions of deaths annually and is attributed to multiple adverse birth outcomes, such as obesity, lung malfunction, and asthma (Hsu et al 2020 ; Toriba and Hayakawa 2021 ). The Global Burden of Diseases in 2019 indicated that particulate matter pollution was the second-leading level 3 risk factor for disability-adjusted life years (DALYs) among all risks.…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution causes millions of deaths annually and is attributed to multiple adverse birth outcomes, such as obesity, lung malfunction, and asthma (Hsu et al 2020 ; Toriba and Hayakawa 2021 ). The Global Burden of Diseases in 2019 indicated that particulate matter pollution was the second-leading level 3 risk factor for disability-adjusted life years (DALYs) among all risks.…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution causes millions of deaths annually and is attributed to multiple adverse birth outcomes, such as obesity, lung malfunction, and asthma (Toriba et al, 2021, Hsu et al, 2020. The Global Burden of Diseases in 2019 indicated that particulate matter pollution was the second-leading Level 3 risk factor for disability-adjusted life years (DALYs) among all risks.…”
Section: Introductionmentioning
confidence: 99%